2015
DOI: 10.1108/he-03-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

A multiple-case study of intersectoral collaboration in comprehensive school health promotion using the DIagnosis of Sustainable Collaboration (DISC) model

Abstract: Purpose – Intersectoral collaboration is often a prerequisite for effective interventions in public health. The purpose of this paper is to assess the facilitating and hindering conditions regarding intersectoral collaboration between health authorities, public health services (PHSs), public services stakeholders (PPSs) and the education sector in comprehensive school health promotion (CSHP) in the Netherlands. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Assessment of the applied models revealed that there was a fairly good variation in studies. The applied models were: DISC (17)(18)(19)(20), Bergen (11,14), Himelman (15), network analysis (16), social network analysis (10,21), act for life collaboration continuum (22), Tukman (23), collective impact approach (24), system analysis (25), and logic (26,27).…”
Section: Results Of the Extraction Of Criteria Models And Indicatorsmentioning
confidence: 99%
“…Assessment of the applied models revealed that there was a fairly good variation in studies. The applied models were: DISC (17)(18)(19)(20), Bergen (11,14), Himelman (15), network analysis (16), social network analysis (10,21), act for life collaboration continuum (22), Tukman (23), collective impact approach (24), system analysis (25), and logic (26,27).…”
Section: Results Of the Extraction Of Criteria Models And Indicatorsmentioning
confidence: 99%
“…The trajectory started with DISC analyses, offering a thorough analysis of facilitating and impeding factors in five regional HSA collaborations spread across the Netherlands. The analyses showed that stakeholders’ positive perceptions about the HSA needed to be more fully translated into positive intentions and real actions and that change management and project management were hardly applied, even though they were considered crucial for this transition [ 19 ]. Based on these diagnoses, we advised the regional coordinators of the five HSA collaborations to focus on the development of effective change management and project management.…”
Section: Methodsmentioning
confidence: 99%
“…The increasing understanding of public health schools as social adaptive systems stimulates the study of intersectoral collaboration in CSHP. This perspective puts an emphasis on the need of joint work between relevant actors at different levels (individual, organizational, policy level) and from various sectors (health, education and authorities) to successfully implement CSHP [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple-case study based on the DISC model In 2008-2011, the DISC model and results of DISC questionnaires were used to support five Dutch regions in the systematic development of intersectoral collaboration in a two-year trajectory. The five HSA collaborations were diagnosed by means of a survey among the relevant stakeholders from health services, PHSs and municipal authorities (Pucher et al, 2015b). Regions independently indicated that adequately situating the HSA within the PHS and positioning it in the region together with PSSs should get priority.…”
Section: Comprehensive School Health Promotionmentioning
confidence: 99%